Mechanical evaluation and optimal mixing ratios in co-disposal of phosphate mining tailings and waste rock - Gabriel Gomes Silva; Rafael Cerqueira Silva (Scientific Reports)
Abstract Given the complexity of the behavior of mining tailings dams built by the technique of hydraulic embankments and the recurring dam ruptures globally, especially in Brazil, ensuring enhanced safety through advanced disposal techniques becomes crucial. While the co-disposal method has been extensively explored for various mineral substances, a notable gap exists in the literature concerning its application specifically to tailings and waste rock generated from phosphate mining operations. This study aims to identify the optimal ratio for a mining tailings and waste rock mixture and evaluate its mechanical behavior in comparison to individual materials. Geotechnical characterization provided essential data for evaluating the applicability of the co-disposal technique. The mechanical behavior was evaluated with direct shear tests, revealing that mixtures exhibit significant improvements in shear strength, particularly in the internal friction angle, compared to pure tailings. The mixtures display cohesion values between those of waste rock and tailings, influenced by suction effects under unsaturated conditions. Microscopic and X-ray analyses further highlight the distinct microstructural characteristics influencing the mechanical behavior of the mixtures. This comprehensive study contributes valuable insights into optimizing co-disposal practices for phosphate ore mining waste, addressing crucial aspects of safety and mechanical behavior in tailings and waste rock mixtures.